Hepatic Epithelioid Hemangioendothelioma Presenting as an Enlarging Vascular Lesion within the Spleen - Juliet A. Emamaullee; Klaudia Nowak; Marla Beach; Julinor Bacani; A. M. James Shapiro (Case Reports in Transplantation)
Epithelioid hemangioendothelioma (EHE) is a rare vascular neoplasm with variable malignant potential that most often presents within the liver. Many patients present with bilobar or extrahepatic disease, and the current treatment paradigm involves liver transplantation, with favorable long term results. Up to 25% of patients are diagnosed incidentally following imaging for other indications, and confirmation of diagnosis requires histologic analysis, as there are no classical imaging features to distinguish hepatic EHE (HEHE) from other solid hepatic lesions. Here we describe a case of microscopic HEHE that was diagnosed following splenectomy for an enlarging vascular tumor within the spleen. Due to the unexpected diagnosis of EHE within the spleen and coexisting but stable appearing liver hemangiomata, a left hepatic lobectomy was performed. Explant histology revealed benign hemangiomata and diffuse, microscopic HEHE. The patient ultimately underwent liver transplantation. HEHE can be a challenging diagnosis, and this case emphasizes that any enlarging vascular lesion, even within the spleen, should prompt a high index of suspicion for HEHE in the setting of known hemangiomata.